UPAYA MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS X IIS 1 SMAN 10 PEKANBARU DENGAN MENERAPKAN PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE - Rusi Ulfa Hasanah Ulfa Hasanah; Atma Murni Atma Murni; Putri Yuanita Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was based on the unsatisfied process in learning mathematics at grade X IIS 1 of SMAN 10 Pekanbaru. It was seen from the low motivation of the students to learn mathematics while the learning process. These problems impact on the number of students who pass the Exponents and Logarithms test with percentage of 2.5%. The research was a Classroom Action Research that aims to improve the learning process and increase the motivation of the students to learn mathematics by implementing Cooperative Learning Approach Structural of Think Pair Square (TPS). There were 40 students in the class consisting 21 boys and 19 girls as the participant of this research. The instruments of data collecting in this research were observation sheets (observation of teacher and students activity and observation of students motivation) and the motivation questionnaire. The observation sheets were analyzed in qualitative descriptive, while the motivation questionnaire were analyzed using the Wilcoxon signed-rank test. The qualitative descriptive showed an improvement of learning process and increased the motivation of students to learn mathematics in the class from before to after the action. The Wilcoxon signed-rank test for all indicators of motivation questionnaire obtained , so that and for each indicator of the motivation to learn mathematics obtained . From this test is rejected, in other words, the motivation to learn mathematics at grade X IIS 1 of SMAN 10 Pekanbaru increased after the action. Based on these results it can be concluded that the application of Cooperative Learning Approach Structural of TPS can improved the learning process and increased motivation to learn mathematics at grade X IIS 1 of SMAN 10 Pekanbaru on first semester of academic year 2014/2015. Key Words : Motivation to Learn Mathematics, Cooperative Learning Approach Structural of Think Pair Square, Classroom Action Research